Critical Pedagogy In Religious Education: Shaping Perspectives On Peace, Justice, And Human Rights - Jasminto Jasminto; Siti Rofi'ah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
This article discusses the integration of Critical Pedagogy and Religious Education to shape students' perspectives on peace, justice, and human rights. By delving into the literature, this research explores the potential impact of Critical Pedagogy on Religious Education. This approach involves students in critical thinking, reflection, and open dialogue regarding religious values to address contemporary social issues. The article examines the key concepts of Critical Pedagogy and its integration into the Religious Education curriculum, aiming to enhance the relevance of religious education. The combination of these two approaches is expected to create students who not only understand religious values but can also apply them to promote peace, justice, and human rights. The conclusion highlights the potential contribution of Critical Pedagogy in shaping a new, responsive paradigm for Religious Education, creating a dynamic learning environment in the face of the complexities of contemporary social challenges. Further research is expected to serve as a solid foundation for positive transformation in religious education and the development of students' perspectives on peace, justice, and human rights